Intrapreneurial Practices and Performance of Cameroonian SMEs (Global Journal of Human-Social Science, 2023)
This study analyzes in the Cameroonian context the influence of intrapreneurship on the performance of SMEs in order to take stock of it and question the levers for accelerating intrapreneurial behavior in this population of companies For this purpose it uses a sample of 131 SMEs extracted from the database of the National Institute of Statistics INS of Cameroon and mobilizes after analyzing descriptive statistics binomial logistic regression models to measure the impact of the variables of intrapreneurship on the financial and economic returns of the SMEs in the sample If the results show that intrapreneurship has a positive effect on performance as has been shown in similar work undertaken in Europe or Africa its implementation remains embryonic in Cameroonian SMEs
Keywords: SME; intrapreneurship; owner-manager; performance